88,944 views
9 votes
9 votes
Is this how you solve this (finding the inverse)

Is this how you solve this (finding the inverse)-example-1
User Tourniquet
by
2.9k points

1 Answer

7 votes
7 votes

There are a couple ways to go about this.

By definition of inverse function, if
j^(-1) exists, then


j\left(j^(-1)(x)\right) = x

All this means is that if you provide some input
x, plug it into
j^(-1)(x), then plug that into
j(x), you end up recovering the original input
x that you started with.

We can also do this in the opposite direction, so


j^(-1)(j(x)) = x

So now if
j(x) is invertible, then


j(x) = -\frac23 x - 9 \implies j\left(j^(-1)(x)\right) = -\frac23 j^(-1)(x) - 9 = x

Solve for
j^(-1).


-\frac23 j^(-1)(x) - 9 = x


\frac23 j^(-1)(x) = -x - 9


j^(-1)(x) = -\frac32 (x+9)


\boxed{j^(-1)(x) = -\frac32 x - \frac{27}2}

Another way to do it is by algebraically substituting
x within the definition of
j(x)

Starting with the given definition


j(x) = -\frac23 x - 9

we replace
x with some new expression in a new variable
y that makes the right side reduce to just
y. To demonstrate, if we multiply
-\frac23 x by
-\frac32, we end up with a coefficient of 1. So let
x=-\frac32 y. Then


j\left(-\frac32 y\right) = -\frac23 \left(-\frac32 y\right) - 9 = y - 9

As you can see, this doesn't completely reduce to
y, so we're not done. To adjust for this, we just add 9 to
y, so our ultimate substitution is
x=-\frac32(y+9). Then


j\left(-\frac32 (y+9)\right) = -\frac23 \left(-\frac32 (y+9)\right) - 9 = (y+9) - 9 = y

Now applying
j^(-1) to both sides,


j^(-1)\left(j\left(-\frac32 (y+9)\right)\right) = j^(-1)(y)


\implies \boxed{j^(-1)(y) = -\frac32 y - \frac{27}2}

(we can freely swap out
y for
x at this point)

Yet another way, since the function here is quite simple, we can just think about the action of
j on a given number
x - multiply it by -2/3, and subtract 9.


x \mapsto -\frac23 x \mapsto -\frac23x - 9 = j(x)

The inverse operation undoes this, so given some number
j(x), we recover
x by adding the additive inverse of -9, or 9, then multiplying the whole result by the multiplicative inverse of -2/3, or -3/2.


j(x) \mapsto j(x) + 9 \mapsto -\frac32(j(x) + 9) \mapsto -\frac32 j(x) - \frac{27}2 = x

You seem to be using some version of this method. You made the mistake of thinking the "multiply by -3/2" step applies only to
j(x), and not
j(x) + 9.

User Andrew Rutter
by
2.9k points